The evaluation of antioxidant and anticancer effects of Lepidium Sativum Subsp Spinescens L. methanol extract on cancer cells - Selek, Sahabettin; Koyuncu, Ismail; Caglar, Hifa Gulru; Bektas, Ibrahim; Yilmaz, Mustafa Abdullah; Gonel, Ataman; Akyuz, Enes (Cellular and Molecular Biology, 2018)
In recent years, there is an increased research interest for plants which are natural sources of antioxidants. Lepidium sativum Subsp spinescens L., commonly found in South West Asia, is a plant known as a healthy nutritional source containing bio-molecules that carry anti-hypertensive, hypoglycemic, anti-asthmatic, antispasmodic, hepato-protective, chemoprotective, anti-inflammatory and anti-oxidant effects. In this study, we aimed to investigate the antioxidant content and activity of Lepidium sativum Subsp spinescens L. methanol extract on cancer cells. Methanol extract of dried Lepidium sativum Subsp spinescens L. was prepared. Total amount of phenolic compounds was determined by Slinkard and Singleton method using Folin-Ciocalteu reagent. Total flavonoid amount was determined according to Zhishen method. Antioxidant activity of the extract was evaluated by CUPRAC and ABTS radical scavenging activity assays. Cytotoxic effects of the plant extract on colon and endometrium cancer cells, and human peripheral lymphocyte cells were investigated in vitro by MTT and neutral red assays. Furthermore, the plant extract was investigated for necrotic effects by LDH assay; apoptotic activity by DNA ladder fragmentation, ELISA and acridine orange/ethidium bromide staining; and genotoxic effect by comet assay methods. Methanol extract of Lepidium sativum Subsp spinescens L. was found to have a high content of phenolic and flavonoid compounds. The extract showed significant antioxidant activity and also cytotoxic activity on colon and endometrium cancer cells in a concentration-dependent manner. Apoptotic activity and genotoxic effects were significantly increased, especially with 200 Î¼g/ml concentrations at 48 hours incubation. In conclusion, it was determined that the extract evaluated in this study could be a natural source of antioxidants. Further molecular studies explaining chemo-preventive and chemotherapeutic effects on cancer cells are required to support anticancer efficacy of the plant.